Fractal segmented lotus shape planar monopole antenna for multiband applications. (2022) - Rao, Saride Jagan Mohan; Dalsania, Piyush C.; Chidurala, Sudharani; Murali Krishna, Ch; Narayan, Puneet; Durga Prasad, D.
Abstract: In this paper, planar monopole antenna in lotus shape is designed and proposed for multiband applications. The overall size of the proposed design is about 28 mm × 35 mm × 1.6 mm. The proposed antenna has been designed on FR − 4 and the dielectric constant of 4.4, thickness of 1.6 mm and loss of tangent is 0.02. Fractal techniques have imposed to increase the number of bands and wide bandwidth. Proposed antenna has multiple resonances at 4.57 GHz, 5.86 GHz, 6.25 GHz, 8.89 GHz, 10.78 GHz, 12.49 GHz and 14.20 GHz and the corresponding impedance bandwidth (IBW) values are 60 MHz, 230 MHz, 140 MHz, 250 MHz, 270 MHz, 460 MHz and 310 MHz. The proposed design has wide fractional bandwidths (FBW) values of 1.3, 3.9, 2.2, 2.8, 2.5, 3.6 and 2.1 and the bandwidth ratio (BR) values are 1.01, 1.03, 1.022, 1.028, 1.025, 1.037 and 1.022. The proposed design achieves the peak gain values at resonant frequencies are 2.56 dB, 3.298 dB, 1.32 dB, 3.89 dB, 6.69 dB, 6.37 dB, and 5.11 dB. At multiple resonances, VSWR values are 1.56, 1.14, 1.30, 1.28, 1.50, 1.04 and 1.57. The applications of the proposed antenna are satellite communications, defense tracking, air traffic control, weather monitoring. The proposed antenna is designed and simulated by using the HFSS software.